Effect of biostimulants and azotofit on peas yield formation - Kolesnikov, Maksym; Колесников, Максим Александрович; Колесніков, Максим Олександрович; Paschenko, Yuliia; Пащенко, Юлия Петровна; Пащенко, Юлія Петрівна; Ponomarenko, S. (My University, 2018)
The aim of the work was to determine the effect of separate and combined application of biostimulants (Stimpo, Regoplant) and bioactivator (Azotofit) on the peas yield formation under the conditions of South Steppe of Ukraine.